ANALISIS LAPORAN KEUANGAN DALAM MENILAI KINERJA KEUANGAN PT. MANDOM INDONSIA TBK TAHUN 2019 - Niken Prasetyowati; Diah Agustina Prihastiwi (JOEL: Journal of Educational and Language Research, 2022)
Purpose - The purpose of this study is to determine the profitability ratios, liquidity ratios, activity ratios, cash flow ratios, solvency ratios and market ratios for the 2019 period. Financial ratio analysis is very important because it can provide an overview for internal and external parties about the good and bad financial condition of a company and the management will obtain information about the company’s strengs and weakness. Research Method – This research method is quantitative, namely secondary data in the form of annual report of PT. Mandom Indonesia Tbk from the Indonesia Stock Exchange (IDX) website. Liquidity ratio analysis uses current ratios, solvency ratios use debt-to-asset ratios and ratios to equity ratios. profitability, activity ratio using return on assets and return on investment, using cash flow ratio and market ratio. Findings - The findings of the analysis of the financial performance of PT. Mandom Indonesia Tbk: 1) Profitability ratios using profit margin in the criteria are moderate, return on assets (ROA) in the criteria are moderator and return on equity (ROE) in the criteria are not good. 2) The liquidity ratio in the Criteria is very good. 3) The activity ratio in the Criteria is not good. 4) The cash flow ratio in the Criteria is not good. 5) Solvency ratio using debt to assets is very good criteria and debt to equity ratio is very good criteria. 6) Market ratio in good Criteria. Implication – This study presents a more complete analysis of financial ratios than previous studies.